Novel fiction and cinematographic fiction in Garabombo, el invisible (1972) by Manuel Scorza - Lassus, Jean-Marie (2023)
The article proposes to approach the second novel of The silent war cycle by Manuel Scorza, formulating the hypothesis of a fictional fiction based on real events, but also thought as a cinematographic fiction. The relationship between fictional fiction and cinematographic fiction is notable in the writing of Garabombo, el invisible and opens up new narrative perspectives for the other novels of an epic cycle whose objective is the future memorization of the heroes in the collective memory.